Post-error adjustment among children aged 7 years with a familial high risk of schizophrenia or bipolar disorder: A population-based cohort study. (17th December 2022) - Burton, Birgitte Klee; Petersen, Anders; Eichele, Heike; Hemager, Nicoline; Spang, Katrine S.; Ellersgaard, Ditte; Christiani, Camilla Jerlang; Greve, Aja; Gantriis, Ditte; Jepsen, Jens Richardt M.; Mors, Ole; Nordentoft, Merete; et al.
Abstract: The cognitive control system matures gradually with age and shows age-related sex differences. To gain knowledge concerning error adaptation in familial high-risk groups, investigating error adaptation among the offspring of parents with severe mental disorders is important and may contribute to the understanding of cognitive functioning in at-risk individuals. We identified an observational cohort through Danish registries and measured error adaptation using an Eriksen flanker paradigm. We tested 497 7-year-old children with a familial high risk of schizophrenia ( N = 192) or bipolar disorder ( N = 116) for deficits in error adaptation compared with a control group ( N = 189). We investigated whether error adaptation differed between high-risk groups compared with controls and sex differences in the adaptation to errors, irrespective of high-risk status. Overall, children exhibited post-error slowing (PES), but the slowing of responses did not translate to significant improvements in accuracy. No differences were detected between either high-risk group compared with the controls. Boys showed less PES and PES after incongruent trials than girls. Our results suggest that familial high risk of severe mental disorders does not influence error adaptation at this early stage of cognitive control development. Error adaptation behavior at age 7 years shows specific sex differences.